The Description Osteichthyes in the Mangrove ecosystem area Teunom District Aceh Jaya - Nurmuhajirah Nurmuhajirah; M. Ali Sarong; Abdullah Abdullah (Universitas Syiah Kuala, 2020)
This study aims to determine the description of Osteichthyes in the Mangrove Ecosystem, Teunom District, Aceh Jaya Regency. The data collection of this research was conducted in January 2020, and data collection used a survey method with a purposive sampling technique. The research location is set at three stations, namely Lung Gayo divided into 2 stations, namely Station 1 and Station 2 and Station 3 located in Rantoe Meureu. Description Osteichthyes was used using the Saanin fish identification key book meanwhile. The results obtained were that there were 20 species, 11 orders, 19 families and 20 genera from the Osteichthyes class in the mangrove ecosystem, and the Osteichthyes class species which were found to have generally large body shape and dark body color. The conclusion obtained is that the description of osteichthyes has different body characteristics for each species.